Lembaga Inspirasi Al-Qur’an (LIA): Analisis Sejarah, Strategi Sosialisasi Dakwah, dan Kolaborasi Intelektual dalam Mengembangkan Literasi Tafsir - Qurrata Aini; M. Aziz Zulhijan; Nafisah Ajami; Miftah Fauzan Azimah; Fani Sefriani; Nine Chintya Ayu Inasti; Dewi Wahyu Sejati; Nuraisah Simamora (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This research aims to analyze the existence and strategic role of the Lembaga Inspirasi Al-Qur’an (LIA) in transforming media-based da'wah into a global tafsir literacy movement. Using a qualitative descriptive approach with data collection techniques through participant observation, in-depth interviews, and digital documentation, this study explores how LIA addresses the challenges of religious literacy among urban communities. The research findings indicate that LIA has successfully developed an integrated da'wah model that combines three main pillars: broadcasting media through the "One Day One Ayat" program on RRI, the production of tafsir literacy (Tafsir Inspirasi, Tafseer of Inspiration, and the Tafsir Muyassar Inspirasi project), and social movements based on waqf. The historical roots of LIA, which began with radio-based da'wah activities in 2006, evolved into a formal institution in 2012 with state recognition through the tashih certification from the Ministry of Religious Affairs of the Republic of Indonesia. The strategy of cross-country intellectual collaboration and a waqf distribution system spanning 24 provinces and 10 countries are key to expanding the reach of this tafsir literacy. The results conclude that LIA's success lies in its moderate thematic tafsir methodology, linguistic innovation (bilingualism), and a systematic operational system in grounding the messages of the Al-Qur’an at the grassroots level dynamically.